Public Expenditure and Financial Accountability Assessment : Federal Democratic Republic of Ethiopia (Tigray National Regional State) - World Bank (World Bank, Washington, DC, 2020)
The objective of the Public Expenditure and Financial Accountability (PEFA) assessment is to review the current performance of the public financial management (PFM) systems, processes, and institutions of the Tigray regional government since the last assessment in 2015. The assessment is aimed at assisting the government in identifying PFM weaknesses that may inhibit effective delivery of services to its citizens and the realization of its development objectives in general. Furthermore, the findings of the PEFA assessment will assist the government in developing a PFM reform strategy and provide the basis for a coherent PFM reform program that can be supported by development partners (DPs), as well as through the government’s own initiatives. The assessment covers the Tigray Region, which is separate and independent from the federal government and qualifies as a subnational government in the PEFA methodology context. The Tigray regional assessment covered regional government budgeted units, extra budgetary units, the Office of the Regional Auditor General (ORAG), regional council, Tigray Chamber of Commerce, and public enterprises. The assessment shows the state of PFM performance of the region at the time of the fieldwork in November 2019.